AI-enabled smart healthcare using biomedical signals - Chaurasiya, Rahul 1987-; Agrawal, Dheeraj 1979-; Pachori, Ram Bilas 1979- (Advances in bioinformatics and biomedical engineering (ABBE) book series, 2022)
"The book will not only cover the mathematical description of the AI- and ML-based methods; it will also analyze and demonstrate the usability of different AI methods for a range of biomedical signals.